2015
DOI: 10.1016/j.hrtlng.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' perceptions of the Thrombolysis in Myocardial Infarction (TIMI) risk score in older adults with acute myocardial infarction

Abstract: Objectives To evaluate physician-perceived strengths and limitations of the Thrombolysis In Myocardial Infarction (TIMI) risk scores for use in older adults with acute myocardial infarction (AMI). Background The TIMI risk scores are risk stratification models developed to estimate mortality risk for patients hospitalized for AMI. However, these models were developed and validated in cohorts underrepresenting older adults (≥75 years). Methods Qualitative study using semi-structured telephone interviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…At present, the TIMI risk score is the most commonly used means to assess acute ACS prognosis in clinic, which is a summary of 15,000 cases of STEMI patients who underwent thrombolytic therapy, including historical data, hemodynamic parameters, electrocardiogram indicators, and clinical treatment and development. A number of studies have confirmed that TIMI scores are closely correlated with acute ACS cases, and have a good correlation with the long-term prognosis of the incidence of adverse events ( 14 , 15 ). In the present study, in the 4D-STI and TIMI risk score system, as the risk assessment score increased, the probability of occurrence of deaths and poor prognosis were substantially increased in the high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 91%
“…At present, the TIMI risk score is the most commonly used means to assess acute ACS prognosis in clinic, which is a summary of 15,000 cases of STEMI patients who underwent thrombolytic therapy, including historical data, hemodynamic parameters, electrocardiogram indicators, and clinical treatment and development. A number of studies have confirmed that TIMI scores are closely correlated with acute ACS cases, and have a good correlation with the long-term prognosis of the incidence of adverse events ( 14 , 15 ). In the present study, in the 4D-STI and TIMI risk score system, as the risk assessment score increased, the probability of occurrence of deaths and poor prognosis were substantially increased in the high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 91%
“…The lack of weighting for the risk factors, while improving usability, decreased TIMI risk score discriminatory performance [ 6 , 67 ]. In addition, there are different scoring systems for STEMI and NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the TIMI Risk Score for patients with UA or NSTEMI is composed of seven equally weighted, binary variables [ 69 ]. Age, aspirin use during the previous seven days, coronary artery disease (CAD) risk factors, known CAD, recent anginal episodes; ST-segment alterations of at least 0.5mm on the ECG at the time of initial presentation, and elevation of serum cardiac markers [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, in the setting of evidence that SDM could improve outcomes including adherence and satisfaction with care, there has been a movement in the health care system to implement SDM across a wide range of practice settings. [29][30][31][32] Cardiologists in our study valued SDM in the setting of older adults hospitalized for NSTEMI, but they noted a lack of specific tools for implementation. On the other hand, patients often only perceived catheterization as a possible choice for treatment, and many would have liked to be more informed.…”
Section: Discussionmentioning
confidence: 99%